STRATEGI PENGEMBANGAN BISNIS TAMMY MART MENGGUNAKAN ANALISIS GENERAL ELECTRIC MATRIX: USAHA RITEL DI KABUPATEN BANYUMAS - Apriza Dika Trikusuma; Ilham Musyafa; Laila Tsamrotul Fuadiah; Wardah Aliya; Yoiz Shofwa Shafrani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This research is motivated by the importance of formulating appropriate business development strategies for local retail businesses in an increasingly competitive market environment. Tammy Mart, as a local retail business in Banyumas Regency, needs to understand its strategic position to maintain business sustainability and improve competitiveness. This study aims to analyze Tammy Mart's strategic position using the General Electric (GE) Matrix, identify the condition of industry attractiveness and business strength, and formulate appropriate business development strategies. The study employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. Data collection was conducted on May 4, 2026, at Tammy Mart, located on Jl. Letjend Pol. Soemarto, Karangjambu, Purwanegara, East Purwokerto District, Banyumas Regency, with Mrs. Utami Dewi as the main informant and business owner. The findings indicate that Tammy Mart possesses moderate to high industry attractiveness and moderate to strong business strength. Based on the General Electric Matrix analysis, the business is positioned in the selective growth area. Recommended strategies include strengthening price competitiveness, optimizing digital marketing, enhancing customer loyalty, expanding product variety, and improving operational efficiency. This study provides practical contributions as a strategic decision-making reference for the development of local retail businesses